A Method to Evaluate Chewing Efficiency in Infants Through Food Bolus Characterization: A Preliminary Study. Issue 2 (28th March 2015) - Tournier, C.; Rodrigues, J.; Canon, F.; Salles, C.; Feron, G.
Abstract Chewing skills develop greatly during the two first years of life, but the evolution of masticatory efficiency has never been directly measured so far. A bottleneck for such study is the difficulty in using the chew‐and‐spit method with infants and very young children. Herein, we propose a new method based on a model gel enclosed in a food feeder, which has been assessed with adult subjects. Subjects chewed and compressed the gel either alone or enclosed in two different feeders. Analysis of the number of particles and particle area distribution revealed that one feeder, made from silicone teat, interfered with bolus breakdown. However, similar results were observed between experiments in a feeder made from tissue mesh and in natural condition (unbagged). This method allows easy collection of bolus and is infant friendly; it can be used in future experiments as an alternative to chew‐and‐spit method for studying masticatory efficiency in infancy. Practical Applications This paper proposes for the first time a method that could be used to quantify masticatory efficiency in infants. More generally, the approach based on feeder could be used for collecting boluses as an alternative when chew‐and‐spit is impracticable.